2005
DOI: 10.1111/j.1360-0443.2005.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Family members of relatives with alcohol, drug and gambling problems: a set of standardized questionnaires for assessing stress, coping and strain

Abstract: A set of standard measures is available for helping to assess the needs of concerned and affected family members, derived from an explicit model of the family in relation to excessive drinking, drug taking or gambling. It may have a role to play in correcting the current neglect of the needs of such family members, estimated to be in the region of nearly a million adults in Britain alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
6
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(148 citation statements)
references
References 57 publications
7
125
6
9
Order By: Relevance
“…The most common strategies family members reported were related to financial control and supportive engagement. Other studies also show family members of problem gamblers most often engage in controlling strategies, such as exercising control of the finances and searching for evidence of gambling (Krishnan & Orford, 2002;Orford et al, 2005). Although avoidance and withdrawal have been demonstrated in previous research on problem gamblers (Orford et al, 2005), they were the least commonly reported strategies in the current study.…”
Section: Discussioncontrasting
confidence: 42%
“…The most common strategies family members reported were related to financial control and supportive engagement. Other studies also show family members of problem gamblers most often engage in controlling strategies, such as exercising control of the finances and searching for evidence of gambling (Krishnan & Orford, 2002;Orford et al, 2005). Although avoidance and withdrawal have been demonstrated in previous research on problem gamblers (Orford et al, 2005), they were the least commonly reported strategies in the current study.…”
Section: Discussioncontrasting
confidence: 42%
“…A pool of 87 items was generated from previous research and discussion with gambling service providers (Gamblers Help services in Victoria, Australia). In line with related areas of research, items were multidimensional and included measurement of marital, legal, medical, financial, interpersonal relationships, social, emotional, and psychological issues (Kirby et al 2005;Orford et al 2005;Stein and Riessman 1980). These items were then reviewed by the research team and examined by two leading experts in the field of gambling clinical practice research.…”
Section: Family Impacts Of Problem Gamblingmentioning
confidence: 99%
“…These include a brief scale that has been specifically designed to measure the financial impact of gambling on the family (Abbott and Cramer 1993), the 16-item Family Member Impact (FMI) scale (Orford et al 2005) measuring two different aspects of perceived impacts (worry behavior characterized by disruption of family financial and social life and concern for the family member's health and wellbeing; and active disturbance characterised by the family member's moodiness and aggression), and the 43-item Inventory of Consequences Scale for the Gambler and the Concerned Significant Other (CSO) (Hodgins et al 2007a) which is comprised of three subscales (Gambler Consequences, CSO Emotional Consequences, and CSO Behavioural Consequences). These scales are generally limited by a failure to measure family impacts across multiple domains, being based on the consequences of substance abuse that may not be relevant for gambling populations, the inclusion of impacts of the individual gambler as well as their family members, and impractical lengths, particularly for research purposes.…”
Section: Introductionmentioning
confidence: 99%
“…More extensive lists that concentrate on a specific dimension of third-party problems such those experienced by family members (e.g. Orford, Templeton, Vellemann, & Copello, 2005) or as intimate partner violence (Bergmark, Graham, & Nordvik, 2005) are few and little research, as mentioned, is to be found in the literature.…”
Section: Social Consequencesmentioning
confidence: 99%